Q. 15.0( 2 Votes )

Solve the followi

Answer :

We have,

2x + 3y = 9 …(i)

3x + 4y = 5 …(ii)

From equation (i),

2x + 3y = 9

2x = 9 – 3y


Substituting the value of x from equation (iii) in equation (ii), we get

27 – y = 10

y = 27 – 10

y = 17

Putting this value of y in equation (iii), we get

x = -21

Thus, we get the solution as x = -21 and y = 17.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Subject Verb AgreementSubject Verb AgreementSubject Verb Agreement36 mins
TensesTensesTenses41 mins
VoiceVoiceVoice40 mins
Comma SpliceComma SpliceComma Splice41 mins
RedundancyRedundancyRedundancy38 mins
Mixed BagMixed BagMixed Bag40 mins
Dangling ModifierDangling ModifierDangling Modifier43 mins
Mix Bag QuestionsMix Bag QuestionsMix Bag Questions40 mins
Integrated GrammarIntegrated GrammarIntegrated Grammar43 mins
Reported SpeechReported SpeechReported Speech45 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses